ChemInform Abstract: A Cobalt‐Catalyzed Alkene Hydroboration with Pinacolborane. Issue 33 (19th August 2014) - Zhang, Lei; Zuo, Ziqing; Leng, Xuebing; Huang, Zheng
Abstract The preparation of PNN pincer cobalt complexes like (I) and their application in alkene hydroborations are described.